Effect of posture on oxygenation and respiratory muscle strength in convalescent infants. Issue 3 (1st May 2002) - Dimitriou, G; Greenough, A; Pink, L; McGhee, A; Hickey, A; Rafferty, G F
Abstract : Objective: To determine if differences in respiratory muscle strength could explain any posture related effects on oxygenation in convalescent neonates. Methods: Infants were examined in three postures: supine, supine with head up tilt of 45°, and prone. A subsequent study was performed to determine the influence of head position in the supine posture. In each posture/head position, oxygen saturation (Sao 2 ) was determined and respiratory muscle strength assessed by measurement of the maximum inspiratory pressure (Pimax ). Patients: Twenty infants, median gestational age 34.5 weeks (range 25–43), and 10 infants, median gestational age 33 weeks (range 30–36), were entered into the first and second study respectively. Results: Oxygenation was higher in the prone and supine with 45° head up tilt postures than in the supine posture (p<0.001), whereas Pimax was higher in the supine and supine with head up tilt of 45° postures than in the prone posture (p<0.001). Head position did not influence the effect of posture on Pimax or oxygenation. Conclusion: Superior oxygenation in the prone posture in convalescent infants was not explained by greater respiratory muscle strength, as this was superior in the supine posture.